Using trusted platform module for securing virtual environment access in cloud - Sherif, Asser (AUC Knowledge Fountain, 2015)
With the increasing usage of Cloud and the Virtualization technology, there comes also an increasing demand to ensure the security levels of all computing environments and components associated and accordingly in this work we propose a new machine authentication mechanism using Trusted Platform Module that can be used to provide a secure access to virtual environments in the cloud. The proposed authentication module is aiming to contribute in providing a solution to Poor machine identity, Multi-tenancy as well as Malicious insiders known security problems in the cloud. It is targeting the access security to graphical user interface of virtual machines hosted on VirtualBox hypervisor in a Linux based environment through authenticating clients trying to connect using the client's Trusted Platform Module Public Endorsement key as a pre-authorized signature to the virtual environment in addition to the normal user name and password authentication of the connecting user. Results obtained from the output of this work indicates that it is possible to authenticate the machines based on their Trusted Platform Module signatures and provide them access to VirtualBox environment only based on a pre-defined Access Control List with minimal one time overhead upon establishing the initial connection.